2004
DOI: 10.1542/peds.114.2.404
|View full text |Cite
|
Sign up to set email alerts
|

Bias in Reported Neurodevelopmental Outcomes Among Extremely Low Birth Weight Survivors

Abstract: ELBW infant survivors who weighed 401 to 1000 g at birth and who are compliant with follow-up evaluations may have worse Bayley Scales of Infant Development, 2nd edition, MDI scores than infants with no visit. Thus, follow-up studies based on infants who are compliant with follow-up care may lead to an overestimation of adverse outcomes in ELBW survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
55
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 41 publications
11
55
1
3
Order By: Relevance
“…Castro et al 14 and McCormick et al, 4 on the other hand, found that compared with children who were lost to follow-up, those who were compliant with follow-up had more adverse outcomes. It seems that the adolescents with higher completed or current education are overrepresented in the full-response group at the age of 19 years.…”
Section: Discussionmentioning
confidence: 99%
“…Castro et al 14 and McCormick et al, 4 on the other hand, found that compared with children who were lost to follow-up, those who were compliant with follow-up had more adverse outcomes. It seems that the adolescents with higher completed or current education are overrepresented in the full-response group at the age of 19 years.…”
Section: Discussionmentioning
confidence: 99%
“…This might bias the mortality results, because the event rate was low and the subjects lost to follow-up monitoring might be at either higher or lower risk of death. 18 On the basis of the generalized estimated equation model used to impute missing deaths, the effect of ENC training might be even larger than demonstrated. Further- …”
Section: Discussionmentioning
confidence: 99%
“…Os dados relativos ao status neuropsicológico dos recém-nascidos prematuros estão disponíveis na literatura, mas a maioria desses estudos foi realizada em países desenvolvidos 4,5,7,[9][10][11][12] . Poucos estudos de acompanhamento foram publicados sobre desempenho escolar ou pré-escolar de lactentes prematuros de baixíssimo peso ao nascimento envolvendo populações sul-americanas 8 , em que recursos de saúde especializados para acompanhar essa população em especial não costumam estar disponíveis.…”
Section: Introductionunclassified